Substrate having pattern film for solid state image sensor
A patterned film substrate with a specific photosensitive composition enables controlled separation and adhesion in solid-state image sensors, addressing lamination issues and improving yield and cost-effectiveness.
Patent Information
- Application Number
- JP2023092418
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-05
- Publication Date
- 2024-12-17
AI Technical Summary
Existing methods for producing substrate laminates for solid-state image sensors face challenges such as poor lamination and high adhesiveness due to heating during the lamination process, leading to low yield and increased component costs, making reworking difficult.
A substrate with a patterned film that includes a photosensitive composition containing a cationically polymerizable compound, a radically polymerizable compound, and a photopolymerization initiator, allowing the substrates to be separated by heating to specific temperatures, enabling reworking and improving adhesiveness.
The solution enhances the yield of substrate laminates by allowing for effective peeling and reusing semiconductor substrates, reducing costs and improving adhesiveness through controlled heating and polymerization processes.
Smart Images

Figure 2024174546000007 
Figure 2024174546000008 
Figure 2024174546000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a substrate with a patterned film for a solid-state imaging device. [Background technology]
[0002] Image sensors such as CMOS sensors and CCD sensors are used in digital cameras, smartphones, etc. In recent years, the use of these sensors has increased with the spread of surveillance cameras in automobiles and factories, and there has been an increasing demand for smaller size and higher resolution.
[0003] The substrate laminate constituting the image sensor has a hollow structure in which, for example, a semiconductor element substrate having a light receiving element and a glass substrate are bonded together with an adhesive. The substrate laminate having a hollow structure can be obtained, for example, by applying a liquid adhesive such as an epoxy resin or an acrylic resin to the periphery of the semiconductor element substrate, placing a glass substrate to be a sealing substrate, and then heating the substrate to harden the liquid adhesive. In addition, a method of using a photosensitive composition instead of the liquid adhesive for the purpose of improving the pattern accuracy has also been considered.
[0004] For example, Patent Document 1 describes a method for producing a substrate laminate, which includes a step of forming a coating film by applying a photosensitive composition onto a first substrate (e.g., a glass substrate), a step of patterning the obtained coating film, a step of forming a laminate by laminating the first substrate and a second substrate (e.g., a semiconductor device substrate) via the patterned coating film (hereinafter, sometimes referred to as a "pattern film"), and a step of heating the obtained laminate to bond the first substrate and the second substrate. Patent Document 1 also describes that the photosensitive composition contains a cationic polymerizable compound and a photoacid generator (photocationic polymerization initiator), and that in the step of patterning the coating film, the coating film is irradiated with light through a photomask to bring the exposed portion of the coating film into a semi-cured state, and then the coating film is developed and heat-cured to form a pattern film. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-62048 A Summary of the Invention [Problem to be solved by the invention]
[0006] When manufacturing substrate stacks used in image sensors and the like, errors such as poor lamination of substrates can occur. From the above perspective, image sensors and the like are inspected to determine whether they pass or fail, and "failed" products are usually discarded, but the cost of materials is rising due to the high performance of semiconductor elements, and the impact of yield on costs is large. Therefore, when a product "fails" the inspection, there is a great need to peel off (rework) the substrate, clean the semiconductor substrate, and reuse it to improve yield.
[0007] In the technology described in Patent Document 1, the reaction proceeds due to heating during the lamination process, resulting in high adhesiveness, making rework difficult.
[0008] In view of the above, an object of the present invention is to provide a substrate with a patterned film for a solid-state imaging element, which allows the substrate to be peeled off (reworked) in order to improve the yield of a substrate laminate for a solid-state imaging element. [Means for solving the problem]
[0009] In view of the above circumstances, the present inventors have conducted extensive research and found that the above problems can be solved by the following steps, thereby completing the present invention.
[0010] 1) A substrate having a patterned coating film on a first substrate, The patterned film-attached substrate is intended to be laminated with a second substrate via a patterned coating film to obtain a substrate laminate for a solid-state imaging device; the patterned film-bearing substrate is laminated with a second substrate via the patterned coating film, and then the patterned coating film and the second substrate are heated to a temperature of 50° C. or more and less than 150° C., so that the patterned coating film and the second substrate can be peeled off from each other; A substrate with a patterned film for a solid-state imaging device, in which the adhesiveness can be improved by heating a laminate of a substrate with a patterned film and a second substrate to 150°C or higher to fully cure the patterned coating film.
[0011] 2) The photosensitive composition contains a cationic polymerizable compound, a radical polymerizable compound, and a photopolymerization initiator, and the photopolymerization initiator is a photoradical initiator; The radical polymerizable compound has a (meth)acryloyl group, 2. The substrate with a patterned film for a solid-state imaging device according to 1), wherein the amount of the radically polymerizable compound is 5 parts by mass or more per 100 parts by mass of the cationic polymerizable compound.
[0012] 3) The substrate with a patterned film for a solid-state imaging device according to 2), wherein the amount of the radical polymerizable compound is 200 parts by mass or less with respect to 100 parts by mass of the cationically polymerizable compound.
[0013] 4) The substrate with a patterned film for a solid-state imaging device according to 2) or 3), wherein the cationically polymerizable compound has a polysiloxane structure.
[0014] 5) The substrate with a patterned film for a solid-state imaging device according to any one of 2) to 4), wherein the cationically polymerizable compound contains at least one of an alicyclic epoxy group, a glycidyl group, and an oxetanyl group as a cationically polymerizable group.
[0015] 6) The substrate with a patterned film for a solid-state imaging device according to any one of 2) to 5), wherein the radically polymerizable compound has an isocyanuric ring and the (meth)acryloyl group in one molecule.
[0016] 7) The substrate with a patterned film for a solid-state imaging device according to any one of 2) to 6), wherein the cationically polymerizable compound has, as an alkali-soluble group, one or more selected from the group consisting of a monovalent organic group represented by the following chemical formula (X1), a divalent organic group represented by the following chemical formula (X2), and a phenolic hydroxyl group.
[0017] [ka] 8) The substrate with a patterned film for a solid-state imaging device according to any one of 1) to 8), wherein the first substrate is a glass substrate, and the second substrate is a semiconductor element substrate. Effect of the Invention
[0018] According to the present invention, by providing a substrate with a patterned film that allows the substrate to be peeled off (reworked), the yield of substrate laminates for solid-state imaging devices can be improved. [Brief description of the drawings]
[0019] [Figure 1] FIG. 2 is a cross-sectional view showing steps (A) to (D) of the present invention. [Diagram 2] 4A to 4C are cross-sectional views showing step (E) of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Preferred embodiments of the present invention will be described in detail below, but the present invention is not limited thereto. In addition, all academic and patent documents described in this specification are incorporated herein by reference.
[0021] First, the terms used in this specification will be explained. The term "photoradical polymerization initiator" refers to a compound that generates only radicals as active species upon irradiation with light. The term "active species" includes radicals, cations, and anions. The term "cationically polymerizable group" refers to a functional group that polymerizes in a chain reaction in the presence of a cation. The term "alkali-soluble group" refers to a functional group that increases the solubility in an alkaline solution by interacting with or reacting with an alkali. The term "polysiloxane structure" refers to a structure in which siloxane units (Si-O-Si) are linked. The term "semi-cured state" refers to a state in which the degree of curing can be further increased by a subsequent process (e.g., a heating process). The formation of a pattern film in a semi-cured state is sometimes described as "B-staging." In addition, the process of further curing the pattern film by heating a laminate in which a first substrate and a second substrate are laminated via a semi-cured pattern film, and bonding the first substrate and the second substrate, is sometimes described as "C-staging." "Solids" refers to non-volatile components in a composition, and "total solids" refers to the total amount of components of a composition excluding the solvent.
[0022] Hereinafter, the compound and its derivatives may be collectively referred to by adding "based" after the compound name. When the compound name is followed by "based" to represent the name of a polymer, it means that the repeating unit of the polymer is derived from the compound or its derivative. Acrylates and methacrylates may be collectively referred to as "(meth)acrylates". Acryloyl groups and methacryloyl groups may be collectively referred to as "(meth)acryloyl groups".
[0023] Unless otherwise specified, the components and functional groups exemplified in this specification may be used alone or in combination of two or more kinds.
[0024] The drawings referred to in the following description are intended to illustrate each component in a schematic manner for ease of understanding, and the size, number, shape, etc. of each component shown in the drawings may differ from the actual size, number, shape, etc., for convenience of drawing. Also, for convenience of explanation, in the drawings described later, the same components as those in the drawings described earlier may be given the same reference numerals, and explanations thereof may be omitted.
[0025] <Substrate with patterned film> A substrate with a patterned film for a solid-state imaging device according to an embodiment of the present invention is a substrate with a patterned film having a patterned coating film on a first substrate, the patterned film-attached substrate is to be laminated with a second substrate via a patterned coating film to obtain a substrate laminate for a solid-state imaging device; the patterned film-bearing substrate is laminated with a second substrate via the patterned coating film, and then the patterned coating film and the second substrate are heated to a temperature of 50° C. or more and less than 150° C., so that the patterned coating film and the second substrate can be peeled off from each other; The laminate of the patterned film-attached substrate and the second substrate is heated to 150° C. or higher to fully cure the patterned coating film and improve adhesion. (The patterned film-attached substrate for solid-state imaging devices may be hereinafter referred to as the patterned film-attached substrate.) The substrate with a patterned film according to the embodiment of the present invention desirably has physical properties within the ranges described below, from the viewpoint of applicability to substrate lamination processes and rework processes.
[0026] In order to ensure the adhesion of the pattern film surface (adhesion to other substrates) in a substrate with a pattern film, the surface elastic modulus of the pattern film measured at 100°C is preferably 70 MPa or less, more preferably 50 MPa or less, even more preferably 20 MPa or less, even more preferably 15 MPa or less, and particularly preferably 10 MPa or less.
[0027] From the viewpoint of reworkability, the reaction initiation temperature of the pattern film in the B-stage state is preferably high. Specifically, it is preferably 50° C. or higher, more preferably 100° C. or higher, and even more preferably 150° C. or higher. On the other hand, if the reaction initiation temperature is too high, it becomes difficult to change the film into the C-stage, so the reaction initiation temperature is preferably 300° C. or lower. The reaction initiation temperature can be determined by an analysis method such as a differential scanning calorimeter (DSC).
[0028] In order to soften the pattern film by heating during rework and to enable peeling from the substrate, the Tg of the pattern film in the B-stage state must be lower than the reaction initiation temperature. Specifically, it is preferably 120°C or lower, more preferably 80°C or lower, and even more preferably 50°C or lower. If the Tg is too low, tackiness appears on the pattern film surface at room temperature, increasing the risk of foreign matter adhesion, so it is preferably -30°C or higher, more preferably 10°C or higher, and even more preferably 30°C or higher. Tg can be determined using a DSC or a dynamic viscoelasticity device.
[0029] A substrate with a patterned film having the above-described physical properties can be obtained by photolithography using the photosensitive composition described below.
[0030] <Photosensitive composition> The photosensitive composition according to an embodiment of the present invention contains a cationic polymerizable compound (hereinafter sometimes referred to as "component (A)"), a radically polymerizable compound (hereinafter sometimes referred to as "component (B)"), and a photopolymerization initiator (hereinafter sometimes referred to as "component (C)"), and component (C) is a photoradical polymerization initiator. Component (A) has a cationic polymerizable group and an alkali-soluble group in one molecule. Component (B) has a (meth)acryloyl group. The amount of component (B) is preferably 5 parts by mass or more relative to 100 parts by mass of component (A).
[0031] The above phrase "the photosensitive composition contains a photopolymerization initiator (component (C)), and component (C) is a photoradical polymerization initiator" means that the photosensitive composition contains a photoradical polymerization initiator, and the content of a photopolymerization initiator other than the photoradical polymerization initiator (e.g., a photocationic polymerization initiator, etc.) is less than 0.001 part by mass (preferably less than 0.0001 part by mass) per 100 parts by mass of component (A) in the photosensitive composition.
[0032] The photosensitive composition according to the embodiment allows lamination and reworking of substrates via a pattern film made of the photosensitive composition, the reason for which is presumed to be as follows.
[0033] The photosensitive composition according to the embodiment includes a component (A) having a cationic polymerizable group and an alkali-soluble group in one molecule, a component (B) having a (meth)acryloyl group, and a component (C), and the component (C) is a photoradical polymerization initiator. As a result, when the photosensitive composition according to the first embodiment is used for B-staging (exposure), only radicals are generated as active species by light irradiation, and the component (B) in the exposed portion undergoes radical polymerization, so that a pattern film in a semi-cured state can be formed without generating cations. Therefore, according to the photosensitive composition according to the first embodiment, even if a substrate that has been completed up to the B-stage is stored for a long time until it is made into a C-stage, further curing of the pattern film caused by the remaining cations can be suppressed. Therefore, the photosensitive composition according to the embodiment can maintain the semi-cured state of the pattern film. Therefore, even if the first substrate and the second substrate are laminated in the lamination process, the reaction does not proceed, so that rework is possible by heating the pattern film made of the photosensitive composition to a temperature above the Tg to soften it. In the C-stage process, the first and second substrates are laminated together via the pattern film that is maintained in a semi-cured state, and the laminate is then heated to cationic polymerize component (A) in the pattern film, thereby bonding the first and second substrates together.
[0034] In addition, the photosensitive composition according to the embodiment has a relatively large number of reaction sites for radical polymerization because the amount of component (B), which is a curing component when the composition is brought into the B stage, is 5 parts by mass or more per 100 parts by mass of component (A). This makes it possible to increase the alkali resistance of the semi-cured exposed area. Therefore, the photosensitive composition according to the embodiment can suppress film loss during development.
[0035] In an embodiment, in order to further suppress film loss during development, the amount of component (B) is preferably 8 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 20 parts by mass or more, and even more preferably 30 parts by mass or more, relative to 100 parts by mass of component (A).
[0036] In an embodiment, in order to increase the adhesion of the pattern film during C-staging, the amount of component (B) is preferably 200 parts by mass or less, more preferably 150 parts by mass or less, even more preferably 100 parts by mass or less, even more preferably 90 parts by mass or less, particularly preferably 80 parts by mass or less, and may be 70 parts by mass or less, relative to 100 parts by mass of component (A).
[0037] Each component contained in the photosensitive composition according to the embodiment will be described in detail below.
[0038] [Component (A)] The component (A) is not particularly limited as long as it has a cationic polymerizable group and an alkali-soluble group in one molecule. When the component (A) has a cationic polymerizable group and an alkali-soluble group in one molecule, a photosensitive composition excellent in both patterning property and curing property can be obtained. The component (A) preferably has a plurality of cationic polymerizable groups in one molecule. When the component (A) has a plurality of cationic polymerizable groups in one molecule, a cured material layer having a high crosslinking density is obtained, and as a result, the heat resistance of the cured material layer tends to be improved. The plurality of cationic polymerizable groups may be the same type or may be two or more different functional groups. In addition, the component (A) preferably has a plurality of alkali-soluble groups in one molecule. When the component (A) has a plurality of alkali-soluble groups in one molecule, the removability of the non-exposed part during development is increased, and therefore the patterning property tends to be improved. The plurality of alkali-soluble groups may be the same type or may be two or more different functional groups.
[0039] Examples of the cationic polymerizable group contained in component (A) include an epoxy group, a vinyl ether group, an oxetane group, and an alkoxysilyl group. From the viewpoint of storage stability of the photosensitive composition, the cationic polymerizable group preferably contains at least one of an alicyclic epoxy group, a glycidyl group, and an oxetanyl group, and among these, an epoxy group is more preferable, and one or more selected from the group consisting of an alicyclic epoxy group and a glycidyl group are even more preferable. Among these, an alicyclic epoxy group is particularly preferable because it has a relatively high reactivity during curing and can suppress the curing shrinkage of the cured layer.
[0040] Examples of the alkali-soluble group contained in component (A) include a monovalent organic group represented by the following chemical formula (X1) (hereinafter, sometimes referred to as "X1 group"), a divalent organic group represented by the following chemical formula (X2) (hereinafter, sometimes referred to as "X2 group"), a phenolic hydroxyl group, a carboxyl group, and the like. It is preferable that the group is at least one selected from the group consisting of a monovalent organic group represented by the following chemical formula (X1), a divalent organic group represented by the following chemical formula (X2), and a phenolic hydroxyl group. The X1 group is a monovalent organic group derived from N-monosubstituted isocyanuric acid. The X2 group is a divalent organic group derived from N,N'-disubstituted isocyanuric acid.
[0041] [ka] In order to more stably maintain the semi-cured state of the pattern film, the alkali-soluble group in component (A) is preferably one or more selected from the group consisting of X1 group, X2 group, and phenolic hydroxyl group. In order to more stably maintain the semi-cured state of the pattern film, the alkali-soluble group in component (A) is preferably one or more selected from the group consisting of X1 group and X2 group, and more preferably X2 group. Since X1 group and X2 group have relatively low acidity, the progress of cationic polymerization in the pattern film can be suppressed even if the substrate that has completed the B stage is stored for a long time.
[0042] In order to improve the heat resistance of the cured layer, it is preferable that the component (A) contains a polymer skeleton structure. Examples of the polymer skeleton structure include the main chain structures of polymers such as polyacrylic, polyphenol, polyamide, polyanhydride, polycarbonate, polydiene, polyester, polyhaloolefin, polyimide, polyimine, polyketone, polyolefin, polyether, polyphenylene, polyphosphazene, polysiloxane, polysilane, polystyrene, polysulfide, polysulfone, polyurethane, polyurea, and polyvinyl.
[0043] In order to further improve the heat resistance of the cured layer, the component (A) preferably has a polysiloxane structure, more preferably is a polymer having a polysiloxane structure in the main chain, and even more preferably is a polymer having a cyclic polysiloxane structure in the main chain. The "cyclic polysiloxane structure" refers to a cyclic molecular structure skeleton having a siloxane unit (Si-O-Si) as a ring component.
[0044] The cyclic polysiloxane structure may be a monocyclic structure or a polycyclic structure. The polycyclic structure may be a polyhedral structure. Among the siloxane units constituting the ring, the T unit (XSiO 3 / 2 ) or Q units (SiO 4 / 2 The higher the content of the M unit (XSiO 1 / 2 ) or D unit (X2SiO 2 / 2 The higher the content of ), the more flexible the resulting cured layer tends to be and the more reduced the residual stress.
[0045] When component (A) is a polymer having a polysiloxane structure in the main chain, the weight average molecular weight of the polymer is preferably 10,000 to 50,000, more preferably 20,000 to 40,000, and even more preferably 25,000 to 35,000. When the weight average molecular weight is 10,000 or more, a cured layer having excellent heat resistance tends to be obtained. On the other hand, when the weight average molecular weight is 50,000 or less, the removability of the non-exposed part during development is increased, so that the patterning property tends to be improved.
[0046] Component (A) having a polysiloxane structure (more specifically, a cationically polymerizable compound having a cationically polymerizable group, an alkali-soluble group, and a polysiloxane structure in one molecule) can be obtained, for example, by a hydrosilylation reaction using the following compounds (α), (β), and (γ) as starting materials. Compound (α): A polysiloxane compound having at least two SiH groups (hydrosilyl groups) in one molecule. Compound (β): A compound having a carbon-carbon double bond reactive with a SiH group and a cationic polymerizable group in one molecule. Compound (γ): A compound that has a carbon-carbon double bond reactive with SiH groups and an alkali-soluble group in one molecule.
[0047] (Compound (α)) The compound (α) is a polysiloxane compound having at least two SiH groups in one molecule, and for example, compounds described in International Publication No. 96 / 15194 having at least two SiH groups in one molecule can be used. Specific examples of the compound (α) include a hydrosilyl group-containing polysiloxane having a linear structure, a polysiloxane having a hydrosilyl group at the molecular end, and a cyclic polysiloxane having a hydrosilyl group (hereinafter, sometimes simply referred to as "cyclic polysiloxane"). The cyclic polysiloxane may have a polycyclic structure, and the polycyclic structure may be a polyhedral structure. In order to form a cured layer having high heat resistance and mechanical strength, it is preferable to use a cyclic polysiloxane having at least two SiH groups in one molecule as the compound (α). The compound (α) is preferably a cyclic polysiloxane having three or more SiH groups in one molecule. From the viewpoint of heat resistance and light resistance, it is preferable that the group present on the Si atom is either a hydrogen atom or a methyl group.
[0048] Examples of hydrosilyl group-containing polysiloxanes having a linear structure include copolymers of dimethylsiloxane units, methylhydrogensiloxane units, and terminal trimethylsiloxy units, copolymers of diphenylsiloxane units, methylhydrogensiloxane units, and terminal trimethylsiloxy units, copolymers of methylphenylsiloxane units, methylhydrogensiloxane units, and terminal trimethylsiloxy units, and polysiloxanes whose ends are blocked with dimethylhydrogensilyl groups.
[0049] Polysiloxanes having hydrosilyl groups at the molecular terminals include polysiloxanes whose terminals are blocked with dimethylhydrogensilyl groups, and polysiloxanes having a dimethylhydrogensiloxane unit (H(CH3)2SiO 1 / 2 units), and SiO2 units, SiO 3 / 2 Examples of the siloxane include polysiloxanes consisting of one or more siloxane units selected from the group consisting of SiO units and SiO units.
[0050] The cyclic polysiloxane is represented, for example, by the following general formula (1).
[0051] [ka] In general formula (1), R 1 , R 2 and R 3 each independently represents a monovalent organic group having 1 to 20 carbon atoms, m represents an integer of 2 to 10, and n represents an integer of 0 to 10. In order to easily carry out the hydrosilylation reaction, it is preferable that m is 3 or more. In order to easily carry out the hydrosilylation reaction, it is preferable that m+n is 3 or more and 12 or less. In order to more easily carry out the hydrosilylation reaction, it is preferable that n is 0.
[0052] R 1 , R 2 and R 3 R is preferably an organic group composed of an element selected from the group consisting of C, H, and O. 1 , R 2 and R 3 Examples of R include alkyl groups, hydroxyalkyl groups, alkoxyalkyl groups, oxyalkyl groups, and aryl groups. Among these, chain alkyl groups such as methyl groups, ethyl groups, propyl groups, hexyl groups, octyl groups, decyl groups, and dodecyl groups, cyclic alkyl groups such as cyclohexyl groups and norbornyl groups, and phenyl groups are preferred. From the viewpoint of availability of cyclic polysiloxanes, R 1 , R 2 and R 3R is preferably a chain alkyl group having 1 to 6 carbon atoms or a phenyl group. 1 , R 2 and R 3 As the alkyl group, a chain alkyl group having 1 to 6 carbon atoms is preferable, and a methyl group is more preferable.
[0053] Examples of cyclic polysiloxanes represented by general formula (1) include 1,3,5,7-tetrahydrogen-1,3,5,7-tetramethylcyclotetrasiloxane, 1-propyl-3,5,7-trihydrogen-1,3,5,7-tetramethylcyclotetrasiloxane, 1,5-dihydrogen-3,7-dihexyl-1,3,5,7-tetramethylcyclotetrasiloxane, 1,3,5-trihydrogen-1,3,5-trimethylcyclotrisiloxane, 1,3,5,7,9-pentahydrogen-1,3,5,7,9-pentamethylcyclopentasiloxane, and 1,3,5,7,9,11-hexahydrogen-1,3,5,7,9,11-hexamethylcyclohexasiloxane. Among these, from the viewpoints of availability and reactivity of the SiH group, 1,3,5,7-tetrahydrogen-1,3,5,7-tetramethylcyclotetrasiloxane (in the general formula (1), m=4, n=0, and R 1 is a methyl group).
[0054] Compound (α) can be obtained by a known synthesis method. For example, the cyclic polysiloxane represented by general formula (1) can be synthesized by the method described in International Publication No. 96 / 15194. The cyclic polysiloxane having a polyhedral skeleton can be synthesized by the method described in Japanese Patent Application Laid-Open No. 2004-359933, Japanese Patent Application Laid-Open No. 2004-143449, Japanese Patent Application Laid-Open No. 2006-269402, etc. In addition, a commercially available polysiloxane compound may be used as compound (α).
[0055] (Compound (β)) Compound (β) is a compound having a carbon-carbon double bond reactive with a SiH group (hydrosilyl group) and a cationic polymerizable group in one molecule. The cationic polymerizable group in compound (β) is the same as the cationic polymerizable group in component (A) described above, and the preferred embodiments are also the same. That is, compound (β) preferably has an epoxy group as the cationic polymerizable group, more preferably has one or more selected from the group consisting of an alicyclic epoxy group and a glycidyl group, and further preferably has an alicyclic epoxy group.
[0056] Examples of the group containing a carbon-carbon double bond reactive with a SiH group (hereinafter, sometimes simply referred to as an "alkenyl group") include a vinyl group, an allyl group, a methallyl group, a 2-allylphenyl group, a 3-allylphenyl group, a 4-allylphenyl group, a 2-(allyloxy)phenyl group, a 3-(allyloxy)phenyl group, a 4-(allyloxy)phenyl group, a 2-(allyloxy)ethyl group, a 2,2-bis(allyloxymethyl)butyl group, a 3-allyloxy-2,2-bis(allyloxymethyl)propyl group, a vinyl ether group, etc. From the viewpoint of reactivity with a SiH group, it is preferable that the compound (β) has, as an alkenyl group, one or more selected from the group consisting of a vinyl group and an allyl group.
[0057] Specific examples of the compound (β) include 1-vinyl-3,4-epoxycyclohexane, allyl glycidyl ether, diallyl monoglycidyl isocyanurate, monoallyl diglycidyl isocyanurate, etc. From the viewpoint of reactivity in cationic polymerization, the compound (β) is preferably a compound having an alicyclic epoxy group, and particularly preferably 1-vinyl-3,4-epoxycyclohexane.
[0058] (Compound (γ)) Compound (γ) is a compound having a carbon-carbon double bond reactive with a SiH group and an alkali-soluble group in one molecule. The alkali-soluble group in compound (γ) is the same as the alkali-soluble group in component (A) described above, and the preferred embodiments are also the same. That is, compound (γ) preferably has one or more alkali-soluble groups selected from the group consisting of X1 group, X2 group, and phenolic hydroxyl group, more preferably has one or more alkali-soluble groups selected from the group consisting of X1 group and X2 group, and further preferably has X2 group.
[0059] Compound (γ) has a group (alkenyl group) containing a carbon-carbon double bond reactive with a SiH group. Examples of the alkenyl group contained in compound (γ) include the same alkenyl groups as those exemplified as the alkenyl group contained in compound (β) above, and the preferred embodiments are also the same. That is, compound (γ) preferably has one or more alkenyl groups selected from the group consisting of vinyl groups and allyl groups as the alkenyl group.
[0060] Specific examples of the compound (γ) include diallyl isocyanurate, monoallyl isocyanurate, 2,2′-diallyl bisphenol A, vinylphenol, allylphenol, etc. In order to more stably maintain the semi-cured state of the pattern film, the compound (γ) is preferably one or more selected from the group consisting of diallyl isocyanurate, monoallyl isocyanurate, and 2,2′-diallyl bisphenol A, more preferably one or more selected from the group consisting of diallyl isocyanurate and monoallyl isocyanurate, and even more preferably diallyl isocyanurate.
[0061] (Other starting materials) In the hydrosilylation reaction, in addition to the above-mentioned compound (α), compound (β), and compound (γ), other starting materials may be used. For example, as the other starting materials, alkenyl-containing compounds different from the above-mentioned compound (β) and compound (γ) (hereinafter, sometimes referred to as "other alkenyl-containing compounds") may be used.
[0062] In order to obtain a cured layer having excellent heat resistance, it is preferable to use a compound having two or more alkenyl groups in one molecule (hereinafter, sometimes referred to as "compound (δ)") as another alkenyl group-containing compound. If compound (δ) is used, the number of crosslinking points increases during the hydrosilylation reaction, so that the heat resistance of the cured layer obtained by C-staging tends to improve.
[0063] Specific examples of the compound (δ) include diallyl phthalate, triallyl trimellitate, diethylene glycol bisallyl carbonate, 1,1,2,2-tetraallyloxyethane, triallyl cyanurate, triallyl isocyanurate, diallyl monobenzyl isocyanurate, diallyl monomethyl isocyanurate, 1,2,4-trivinylcyclohexane, triethylene glycol divinyl ether, divinylbenzene, divinylbiphenyl, 1,3-diisopropenylbenzene, 1,4-diisopropenylbenzene, 1,3-bis(allyloxy)adamantane, 1,3-bis(vinyloxy)adamantane, 1,3,5-tris(allyloxy)adamantane, 1,3,5-tris(vinyloxy)adamantane, dicyclopentadiene, vinylcyclohexene, 1,5-hexadiene, 1,9-decadiene, diallyl ether, and oligomers thereof.
[0064] In order to further improve the heat resistance of the resulting cured layer, the compound (δ) is preferably diallyl monomethyl isocyanurate.
[0065] In order to further suppress the film loss during development, it is preferable to use a compound having an alkenyl group and a (meth)acryloyl group in one molecule (hereinafter, sometimes referred to as "compound (ε)") as another alkenyl group-containing compound. By using compound (ε), a (meth)acryloyl group is introduced into component (A), so that the number of reaction points for the radical polymerization reaction becomes relatively large. This makes it possible to increase the alkali resistance of the semi-cured exposed area.
[0066] Specific examples of the compound (ε) include vinyl acrylate, vinyl methacrylate, allyl acrylate, allyl methacrylate, 2-butenyl acrylate, 2-butenyl methacrylate, etc. In order to further suppress the film loss during development, the compound (ε) is preferably one or more selected from the group consisting of vinyl acrylate and allyl acrylate, and more preferably allyl acrylate.
[0067] (Hydrosilylation reaction) The order and method of hydrosilylation reaction for obtaining component (A) are not particularly limited. For example, component (A) having a polysiloxane structure can be obtained by hydrosilylation reaction according to the method described in International Publication No. 2009 / 075233 using the above-mentioned compound (α), compound (β), compound (γ), and other starting materials that are optional components as needed. Component (A) obtained using the above-mentioned compound (α), compound (β), compound (γ), and other starting materials that are optional components as needed is, for example, a polymer having a plurality of cationic polymerizable groups and a plurality of alkali-soluble groups in one molecule and having a polysiloxane structure in the main chain.
[0068] The ratio of each compound in the hydrosilylation reaction is not particularly limited, but the total substance amount A of alkenyl groups in the starting materials and the total substance amount B of SiH groups preferably satisfy the relationship 1≦B / A≦30, and more preferably 1≦B / A≦10.
[0069] In order to enhance the heat resistance of the cured layer obtained by C-staging while stably maintaining the semi-cured state of the pattern film, the charge ratio of compound (β) to compound (α) in the hydrosilylation reaction (mass of compound (β) / mass of compound (α)) is preferably 0.1 or more and 1.0 or less, and more preferably 0.2 or more and 0.9 or less.
[0070] In order to obtain a photosensitive composition having excellent patterning properties, the charge ratio of compound (γ) to compound (α) in the hydrosilylation reaction (mass of compound (γ) / mass of compound (α)) is preferably 0.1 or more and 0.9 or less, and more preferably 0.2 or more and 0.8 or less.
[0071] When compound (δ) is used as a starting material, in order to obtain a photosensitive composition having excellent patterning properties while improving the heat resistance of the cured material layer obtained by C-staging, the charge ratio of compound (δ) to compound (α) in the hydrosilylation reaction (mass of compound (δ) / mass of compound (α)) is preferably 0.01 or more and 0.5 or less, and more preferably 0.05 or more and 0.4 or less.
[0072] When compound (ε) is used as a starting material, in order to further suppress film loss during development while ensuring the adhesion of the pattern film during C-staging, the charge ratio of compound (ε) to compound (α) in the hydrosilylation reaction (mass of compound (ε) / mass of compound (α)) is preferably 0.1 or more and 0.5 or less, more preferably 0.2 or more and 0.4 or less.
[0073] For the hydrosilylation reaction, a hydrosilylation catalyst such as chloroplatinic acid, a platinum-olefin complex, or a platinum-vinylsiloxane complex may be used. The hydrosilylation catalyst may be used in combination with a co-catalyst. The amount of the hydrosilylation catalyst (amount of substance) added is not particularly limited, but is preferably 10 to 100% based on the total amount of alkenyl groups contained in the starting material. -8 more than 10 times -1 times or less, more preferably 10 -6 more than 10 times -2 It is less than double.
[0074] The reaction temperature for hydrosilylation may be appropriately set, and is preferably from 30° C. to 200° C., more preferably from 50° C. to 150° C. The oxygen concentration in the gas phase during the hydrosilylation reaction is preferably 3% by volume or less. From the viewpoint of promoting the hydrosilylation reaction, the gas phase may contain 0.1% by volume to 3% by volume of oxygen.
[0075] A solvent may be used in the hydrosilylation reaction. As the solvent, one type of solvent alone or a mixed solvent of two or more types of solvents may be used. Examples of the solvent include hydrocarbon solvents such as benzene, toluene, xylene, hexane, and heptane; ether solvents such as tetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, and diethyl ether; ketone solvents such as acetone and methyl ethyl ketone; and halogen solvents such as chloroform, methylene chloride, and 1,2-dichloroethane. Toluene, xylene, tetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, and chloroform are preferred because they are easily removed by distillation after the reaction. In the hydrosilylation reaction, a gelation inhibitor may be used as necessary.
[0076] [Component (B)] Component (B) is not particularly limited as long as it is a radical polymerizable compound having a (meth)acryloyl group. The radical polymerizable compound having a (meth)acryloyl group includes a compound having at least one acryloyl group and at least one methacryloyl group in one molecule.
[0077] In order to increase the reactivity of the radical polymerization reaction, thereby increasing the alkali resistance of the semi-cured exposed area, and thereby further suppressing film loss during development, a compound having an acryloyl group is preferred as component (B).
[0078] In addition, in order to enhance the alkali resistance of the semi-cured exposed portion by increasing the reactivity of the radical polymerization reaction and further suppress the film loss during development, the component (B) is preferably a compound having two or more (meth)acryloyl groups in one molecule, more preferably a compound having three or more (meth)acryloyl groups in one molecule, and even more preferably a compound having four or more (meth)acryloyl groups in one molecule. In order to particularly suppress the film loss during development, the component (B) is preferably a compound having two or more acryloyl groups in one molecule, more preferably a compound having three or more acryloyl groups in one molecule, and even more preferably a compound having four or more acryloyl groups in one molecule.
[0079] In order to ensure the adhesion of the pattern film during C-staging, the number of (meth)acryloyl groups contained in one molecule of component (B) is preferably 6 or less, more preferably 5 or less, and even more preferably 4 or less.
[0080] Examples of the component (B) having one (meth)acryloyl group per molecule include isoamyl acrylate, lauryl acrylate, octyl acrylate, decyl acrylate, isostearyl acrylate, butoxyethyl (meth)acrylate, ethoxydiethylene glycol acrylate, methoxydiethylene glycol acrylate, methoxytripropylene glycol acrylate, methoxypolyethylene glycol acrylate, phenoxyethyl acrylate, and tetrahydrofurfuryl (meth)acrylate.
[0081] Examples of component (B) having two (meth)acryloyl groups in one molecule include triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate (more specifically, polypropylene glycol #700 diacrylate, etc.), 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, etc.
[0082] Examples of the component (B) having three (meth)acryloyl groups in one molecule include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and glycerin propoxy tri(meth)acrylate.
[0083] Examples of the component (B) having four (meth)acryloyl groups in one molecule include pentaerythritol tetra(meth)acrylate and ditrimethylolpropane tetra(meth)acrylate.
[0084] Component (B) may have a cationic polymerizable group. Component (B) may also have an alkali-soluble group. However, in order to improve the patterning property and more stably maintain the semi-cured state of the pattern film, it is preferable that the photosensitive composition according to the embodiment does not contain a compound having a cationic polymerizable group and an alkali-soluble group in one molecule as component (B). In other words, in the photosensitive composition according to the first embodiment, it is preferable that component (B) is not a compound having a cationic polymerizable group and an alkali-soluble group in one molecule.
[0085] Component (B) preferably has an isocyanuric ring and a (meth)acryloyl group in one molecule. In this case, the cohesive strength of the pattern film is improved, making it easier to suppress cohesive failure of the pattern film during rework. By suppressing cohesive failure of the pattern film, no residue is left on the second substrate, making it easier to reuse.
[0086] [Component (C)] Component (C) is a photoradical polymerization initiator. In order to more stably maintain the semi-cured state of the pattern film, the photoradical polymerization initiator used as component (C) is preferably a compound that does not generate cations when heat-treated in the manufacturing process up to the B-stage, and more preferably a compound that does not generate cations even when heat-treated at a temperature of 200° C. or less for a heating time of 60 minutes or less.
[0087] Specific examples of component (C) include acetophenone compounds, acylphosphine oxide compounds, benzoin compounds, benzophenone compounds, α-diketone compounds, biimidazole compounds, polynuclear quinone compounds, triazine compounds, oxime ester compounds, titanocene compounds, xanthone compounds, thioxanthone compounds, ketal compounds, azo compounds, peroxides, 2,3-dialkyldione compounds, disulfide compounds, fluoroamine compounds, etc. In order to further suppress film loss during development, component (C) is preferably one or more selected from the group consisting of acetophenone compounds, benzophenone compounds, and oxime ester compounds.
[0088] Examples of acetophenone compounds include 1-(4-dodecylphenyl)-2-hydroxy-2-methylpropan-1-one, 2,2-dimethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-(4'-i-propylphenyl)-2-hydroxy-2-methylpropan-1-one, 4-(2'-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, 2,2-dimethoxyacetophenone, 2,2-diethoxyacetophenone, 2-methyl-1-(4'-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4'-morpholinophenyl)butan-1-one, and 1-hydroxycyclohexyl phenyl ketone.
[0089] Examples of the acylphosphine oxide compounds include 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide.
[0090] Examples of oxime ester compounds include 1,2-octanedione 1-[4-(phenylthio)-2-(O-benzoyloxime)], ethanone 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime), and the like.
[0091] Examples of the benzoin compounds include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.
[0092] Examples of the benzophenone compounds include benzyl dimethyl ketone, benzophenone, 4,4'-bis(dimethylamino)benzophenone, and 4,4'-bis(diethylamino)benzophenone.
[0093] An example of the α-diketone compound is methyl benzoyl formate.
[0094] Examples of the biimidazole compound include 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetrakis(4-ethoxycarbonylphenyl)-1,2'-biimidazole, 2,2'-bis(2,4-dichlorophenyl)-4,4',5,5'-tetrakis(4-ethoxycarbonylphenyl)-1,2'-biimidazole, 2,2'-bis(2,4,6-trichlorophenyl)-4,4',5,5'- Tetrakis(4-ethoxycarbonylphenyl)-1,2'-biimidazole, 2,2'-bis(2-bromophenyl)-4,4',5,5'-tetrakis(4-ethoxycarbonylphenyl)-1,2'-biimidazole, 2,2'-bis(2,4-dibromophenyl)-4,4',5,5'-tetrakis(4-ethoxycarbonylphenyl)-1,2'-biimidazole, 2,2'-bis(2,4,6-tribromophenyl)- 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2,2'-bis(2,4-dichlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2,2'-bis(2,4,6-trichlorophenyl)-4,4',5,5 2,2'-bis(2-bromophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2,2'-bis(2,4-dibromophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, and 2,2'-bis(2,4,6-tribromophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole.
[0095] Examples of polynuclear quinone compounds include anthraquinone, 2-ethylanthraquinone, 2-t-butylanthraquinone, and 1,4-naphthoquinone.
[0096] Examples of xanthone compounds include xanthone, thioxanthone, and 2-chlorothioxanthone.
[0097] Examples of triazine compounds include 1,3,5-tris(trichloromethyl)-s-triazine, 1,3-bis(trichloromethyl)-5-(2'-chlorophenyl)-s-triazine, 1,3-bis(trichloromethyl)-5-(4'-chlorophenyl)-s-triazine, 1,3-bis(trichloromethyl)-5-(2'-methoxyphenyl)-s-triazine, 1,3-bis(trichloromethyl)-5-(4'-methoxyphenyl)-s-triazine, 2-(2'-furylethylidene)-4,6-bis(trichloromethyl)-s-triazine, 2-(4'-methoxystyryl)-s-triazine, 2-(4'-methoxystyryl)-4,6-bis(trichloromethyl)-s-triazine, 2-(3',4'-dimethoxystyryl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4'-methoxynaphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(2'-bromo-4'-methylphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(2'-thiophenylethylidene)-4,6-bis(trichloromethyl)-s-triazine, and the like.
[0098] In order to further suppress the film loss during development, the amount of component (C) is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, relative to 100 parts by mass of component (B). Also, in order to ensure the adhesiveness of the pattern film during C-staging, the amount of component (C) is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, relative to 100 parts by mass of component (B).
[0099] [solvent] The photosensitive composition according to the first embodiment may contain a solvent. For example, the photosensitive composition according to the first embodiment can be obtained by dissolving or dispersing the above-mentioned components (A), (B), and (C), and other components described below as necessary, in a solvent.
[0100] Specific examples of the solvent include hydrocarbon solvents such as benzene, toluene, hexane, and heptane; ether solvents such as tetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, and diethyl ether; ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; glycol solvents such as propylene glycol 1-monomethyl ether 2-acetate, diethylene glycol dimethyl ether, diethylene glycol ethyl methyl ether, and ethylene glycol diethyl ether; and halogen solvents such as chloroform, methylene chloride, and 1,2-dichloroethane. From the viewpoint of the coatability (film formation stability) of the photosensitive composition, the solvent is preferably a glycol solvent, and more preferably propylene glycol 1-monomethyl ether 2-acetate.
[0101] From the viewpoint of the coatability (film-forming stability) of the photosensitive composition, the amount of the solvent is preferably 10 parts by mass or more and 200 parts by mass or less, and more preferably 20 parts by mass or more and 100 parts by mass or less, per 100 parts by mass of component (A).
[0102] [Other ingredients] The photosensitive composition according to the embodiment may contain components (other components) other than the above-mentioned components (A), (B) and (C) within the scope of the present invention. However, in order to more stably maintain the semi-cured state of the pattern film while further suppressing the film loss during development, the total amount of components (A), (B) and (C) is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more and 100% by mass or less, based on the total solid content of the photosensitive composition. Examples of other components include thermal cationic polymerization initiators, radical scavengers, colorants, sensitizers, fillers, adhesion improvers, coupling agents such as silane coupling agents, deterioration inhibitors, release agents, flame retardants, flame retardant assistants, surfactants, defoamers, emulsifiers, leveling agents, anti-repellent agents, thixotropy imparting agents, tackifiers, storage stability improvers, light stabilizers, thickeners, plasticizers, reactive diluents, antioxidants, heat stabilizers, electrical conductivity imparting agents, antistatic agents, radiation shielding agents, nucleating agents, lubricants, metal deactivators, and thermal conductivity imparting agents.
[0103] (Thermal cationic polymerization initiator) When the photosensitive composition according to the embodiment contains a thermal cationic polymerization initiator (a compound that generates only cations as active species by heating) as another component, the heating temperature during C-stage can be reduced, and thus, for example, deterioration of the substrate due to heating can be suppressed. The thermal cationic polymerization initiator is preferably a compound whose thermal decomposition temperature is higher than the baking temperature (e.g., 120°C) during B-stage formation or the heating temperature during the rework process, and more preferably a compound whose thermal decomposition temperature is the baking temperature during B-stage formation or the heating temperature during the rework process +5°C or higher. However, in order to more stably maintain the semi-cured state of the pattern film, it is preferable that the photosensitive composition according to the embodiment does not contain a thermal cationic polymerization initiator. Even if the photosensitive composition according to the embodiment does not contain a thermal cationic polymerization initiator, cations are generated from, for example, an alkali-soluble group possessed by component (A) by heating during C-stage formation, so that the pattern film can be thermally cured. The "thermal decomposition temperature" means the temperature at which weight loss due to thermal decomposition of the thermal cationic polymerization initiator begins when the thermal cationic polymerization initiator is subjected to thermogravimetric measurement using a simultaneous differential thermal and thermogravimetric analyzer.
[0104] (Radical scavenger) When the photosensitive composition according to the embodiment contains a radical scavenger as another component, the diffusion of active radicals generated by light irradiation to the non-exposed area during B-staging is suppressed, and as a result, the curing of the non-exposed area is suppressed, so that the generation of residues after development (for example, non-exposed areas that remain without being removed by development) can be suppressed.
[0105] Examples of the radical scavenger include 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl, 2,2,6,6-tetramethylpiperidine-1-oxyl, 4-amino-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-cyano-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-benzoxy-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-methoxy-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-oxo-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-acetamido-2,2,6,6-tetramethylpiperidine-1-oxyl, and bis-(2,2,6,6-tetramethylpiperidine-1-oxyl)-sebacate. In order to further suppress the generation of residues after development, the radical scavenger is preferably 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl.
[0106] In order to suppress film loss during development while further suppressing the generation of residues after development, the amount of the radical scavenger is preferably 0.01 parts by mass or more and 5 parts by mass or less, and more preferably 0.03 parts by mass or more and 3 parts by mass or less, relative to 100 parts by mass of component (B).
[0107] (Coloring agent) When the photosensitive composition according to the embodiment contains a colorant as another component, a cured layer obtained by using the photosensitive composition can be used as, for example, a light-shielding partition wall for suppressing flare and ghost.
[0108] Examples of the colorant include organic pigments, inorganic pigments, dyes, etc. From the viewpoint of heat resistance and coloring properties, it is preferable to use a pigment as the colorant. When forming a black colored pattern such as a partition wall having a light-shielding property, it is preferable to use a black pigment as the colorant. In addition, examples of colored patterns other than the black pattern include a red pattern, a yellow pattern, and a blue pattern.
[0109] As the pigment, those that absorb a wide range of wavelengths in the visible light region are preferred. Among the pigments that absorb a wide range of wavelengths in the visible light region, examples of black organic pigments include anthraquinone-based black pigments, perylene-based black pigments, azo-based black pigments, and lactam-based black pigments. Among these, perylene-based black pigments and lactam-based black pigments are preferred because of their excellent light-shielding properties. Examples of black inorganic pigments include carbon black and black low-order titanium oxynitride. Examples of other inorganic pigments include composite metal oxide pigments, titanium oxide, barium sulfate, lead sulfate, yellow lead, red iron oxide, ultramarine, Prussian blue, chromium oxide, antimony white, zinc sulfide, zinc, manganese purple, cobalt purple, barium sulfate, and magnesium carbonate. Examples of dyes include azo-based compounds, anthraquinone-based compounds, perylene-based compounds, perinone-based compounds, phthalocyanine-based compounds, carbonium-based compounds, and indigoid-based compounds.
[0110] Pigments that can be used to obtain color patterns other than black include chromatic pigments such as red, orange, yellow, green, blue, purple, cyanine, and magenta.
[0111] In order to further suppress flare and ghost, the colorant is preferably a black inorganic pigment, and more preferably carbon black.
[0112] In order to obtain a photosensitive composition that has excellent photopolymerizability when brought to a B-stage while suppressing the generation of residues, flare, and ghosts after development, the amount of the colorant is preferably from 0.1 to 10 parts by mass, more preferably from 0.3 to 7 parts by mass, and even more preferably from 0.3 to 5 parts by mass, relative to 100 parts by mass of component (A).
[0113] In order to more stably maintain the semi-cured state of the pattern film while further suppressing film loss during development, and to enhance the adhesion of the pattern film during C-stage, the photosensitive composition according to the embodiment preferably satisfies the following condition 1, more preferably satisfies the following condition 2, even more preferably satisfies the following condition 3, and even more preferably satisfies the following condition 4. Condition 1: Component (A) has a polysiloxane structure, and the amount of component (B) is 10 parts by mass or more and 200 parts by mass or less per 100 parts by mass of component (A). Requirement 2: The above requirement 1 is satisfied, and component (A) has an alicyclic epoxy group as a cationically polymerizable group. Requirement 3: The above requirement 2 is satisfied, and component (A) has an X2 group as an alkali-soluble group. Requirement 4: The above requirement 3 is satisfied, and component (B) is a compound having two or more acryloyl groups in one molecule.
[0114] <Manufacturing method for solid-state imaging device> The method for producing a substrate laminate for a solid-state imaging device according to an embodiment of the present invention comprises the following steps (A) to (F). (A) a coating step of forming a coating film by coating a photosensitive composition on a first substrate; (B) an exposure step of irradiating the coating film with light through a photomask to form an exposed portion composed of the photosensitive composition in a semi-cured state and a non-exposed portion in the coating film; (C) a developing step of removing the unexposed areas from the first substrate with an alkaline developer to form a patterned coating film on the first substrate; (D) a lamination step of laminating the first substrate and the second substrate via a patterned semi-cured coating film on the first substrate to form a laminate; (E) If the inspection fails, a peeling process (rework process) is performed to peel off the patterned coating film of the first laminate from the second substrate; (F) A final curing process in which the laminate that has passed the inspection is heated to fully cure the patterned semi-cured coating film and improve adhesion.
[0115] Examples of the first substrate and the second substrate include a silicon wafer, a glass substrate, a resin substrate (such as a transparent resin substrate), a ceramic substrate, a semiconductor element substrate, etc. Examples of the semiconductor element substrate include a sensor substrate (more specifically, an image sensor substrate, etc.).
[0116] In particular, it is preferable that the first substrate is a glass substrate, and the second substrate is a semiconductor element substrate.
[0117] The thickness of the first substrate is, for example, 50 μm or more and 2000 μm or less. The thickness of the second substrate is, for example, 50 μm or more and 800 μm or less. The thickness of the cured layer 13 is, for example, 0.01 μm or more and 200 μm or less, preferably 0.1 μm or more and 150 μm or less, and more preferably 5 μm or more and 150 μm or less.
[0118] The substrate stack may be a hollow structure having a hollow portion between the first substrate and the second substrate. In this case, the internal space of the hollow structure may be a sealed space. When the substrate stack has a sealed internal space, the substrate stack is suitable for a semiconductor device constituting an image sensor.
[0119] [Process (A)] Step (A) shown in Fig. 1 is a coating film forming step in which a coating film is formed by applying a photosensitive composition onto a first substrate. Methods for applying the photosensitive composition onto the first substrate include, but are not limited to, spin coating, roll coating, printing, bar coating, and the like. The thickness of the coating film is, for example, 0.01 µm or more and 200 µm or less, preferably 0.1 µm or more and 150 µm or less, and more preferably 5 µm or more and 150 µm or less.
[0120] After the coating film is formed, the coating film may be heated (prebaked) in order to dry the coating film. The heating temperature can be appropriately set, but is preferably 60° C. or higher and 200° C. or lower, and more preferably 80° C. or higher and 150° C. or lower.
[0121] [Process (B)] Step (B) shown in FIG. 1 is an exposure step in which the coating film is irradiated with light through a photomask to form an exposed portion in a semi-cured state and a non-exposed portion in the coating film. In the exposure step, only radicals are generated as active species by light irradiation in the exposed portion, and the radically polymerizable compound in the exposed portion undergoes radical polymerization, thereby forming an exposed portion in a semi-cured state without generating cations. The wavelength of the light irradiated in the exposure step is, for example, in the range of 200 nm to 450 nm. Examples of light sources that can be used in the exposure step include, but are not limited to, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, a high-power metal halide lamp, a xenon lamp, a carbon arc lamp, and a light-emitting diode. The integrated exposure dose of the exposed portion irradiated with light in the exposure step is preferably 1 mJ / cm. 2 More than 50000mJ / cm 2 More preferably, it is 1 mJ / cm or less. 2 More than 20000mJ / cm 2 The following is the result.
[0122] [Process (C)] Step (C) shown in FIG. 1 is a development step in which an alkaline developer is used to remove the non-exposed portion from the first substrate to form a patterned film, which is a coating film patterned on the first substrate. The alkaline developer used in the development step may be an aqueous solution containing an alkaline component. Examples of the alkaline component contained in the alkaline developer include an alkaline organic component and an alkaline inorganic component. Examples of the alkaline organic component include tetramethylammonium hydroxide (hereinafter sometimes referred to as "TMAH") and choline. Examples of the alkaline inorganic component include potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, and lithium carbonate. From the viewpoint of increasing the contrast between the exposed portion and the non-exposed portion, the concentration of the alkaline component in the alkaline developer is preferably 25% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. The temperature of the alkaline developer may be adjusted according to the developability of the coating film. Examples of a method for contacting the alkaline developer with the non-exposed portion include an immersion method, a paddle method, and a spray method.
[0123] After contacting the non-exposed portion with an alkaline developer in the development step, the laminate having the first substrate and the exposed portion (pattern film) may be washed with water and dried. When drying the laminate, for example, moisture on the surface of the laminate after washing with water can be removed by compressed air, natural drying, or the like.
[0124] After the development step and before the lamination step described below, the pattern film may be heated to a degree that does not reduce the adhesiveness of the pattern film. The heating temperature can be appropriately set, but is preferably 40° C. or higher and 200° C. or lower.
[0125] [Process (D)] Step (D) shown in Fig. 1 is a first lamination step in which a first substrate and a second substrate are laminated with a pattern film interposed therebetween to form a laminate. In the lamination step, lamination may be performed while applying a load of, for example, 0.1 kg to 5 kg. Furthermore, lamination may be performed while heating within a range in which the pattern film does not react. For example, by heating within a range of 60°C to 150°C, the reaction of the pattern film does not proceed, and it is possible to peel it off in the rework step described below.
[0126] [Process (E)] Step (E) shown in FIG. 2 is a peeling step (rework step) in which the patterned coating film of the first laminate in which lamination defects or the like occurred in step (D) is peeled off from the second substrate. As a reworking method, there is a method of softening the patterned film by heating it to the glass transition temperature (Tg) or higher of the semi-cured state. If the temperature is too high, the reaction of the patterned film progresses, the adhesion to the second substrate increases, and reworking becomes impossible, so the above temperature is less than 150°C, preferably 140°C or less, more preferably 120°C or less, and even more preferably 100°C or less. The second substrate of the reworked laminate is washed and sent to the lamination step (D) again, and steps (D) and (E) are repeated until the lamination defects are eliminated. At this time, the glass with the patterned film may be reused after reworking, or a new one may be used. There is no limit to the heating time in the reworking, but from the viewpoint of productivity, about 10 seconds to 5 minutes is preferable.
[0127] [Process (F)] Step (F) is a final curing step in which the laminate is heated to fully cure the patterned semi-cured coating film and improve adhesion (not shown). The heating temperature in the final curing step is, for example, 150°C to 300°C, preferably 160°C to 250°C, and more preferably 160°C to 220°C. Through the above steps, a laminate for a solid-state image sensor is obtained. EXAMPLES
[0128] Examples of the present invention will be described below, but the present invention is not limited to the following examples.
[0129] <Synthesis of cationic polymerizable compound> The synthesis method of the cationic polymerizable compounds A1 to A4 will be described below. The weight average molecular weight of the cationic polymerizable compounds A1 to A3 was calculated based on standard polystyrene conversion from a chromatogram measured using a Tosoh Corporation "HLC-8420GPC" (column: Shodex GPC KD-G 4A (one column), Shodex GPC KD-806M (one column)) with N,N-dimethylformamide as a solvent at a flow rate of 1.0 mL / min.
[0130] [Synthesis of cationic polymerizable compound A1] A mixture of 40 g of diallyl isocyanurate, 29 g of diallyl monomethyl isocyanurate, and 264 g of 1,4-dioxane was mixed with 143 μL of a xylene solution of platinum vinyl siloxane complex (Pt-VTSC-3X, a solution containing 3% by mass of platinum, manufactured by Umicore Precious Metals Japan, Inc.) to obtain solution S1. Separately, 88 g of 1,3,5,7-tetrahydrogen-1,3,5,7-tetramethylcyclotetrasiloxane was dissolved in 176 g of toluene to obtain solution S2.
[0131] Then, in a nitrogen atmosphere containing 3% by volume of oxygen, solution S2 was heated to a temperature of 105° C., and solution S1 was added dropwise to solution S2 over a period of 3 hours. After the completion of the addition, the temperature was kept at 105° C. and the mixture was stirred for 30 minutes to obtain solution S3. The reaction rate of the alkenyl group of the compound contained in the obtained solution S3 was calculated as follows: 1 When measured by 1 H-NMR, the reaction rate was 95% or more.
[0132] Separately, 62 g of 1-vinyl-3,4-epoxycyclohexane was dissolved in 62 g of toluene to obtain a solution S4.
[0133] Then, in a nitrogen atmosphere containing 3% by volume of oxygen, solution S3 was heated to a temperature of 105° C., and solution S4 was added dropwise to solution S3 over a period of 1 hour. After the completion of the addition, the temperature was kept at 105° C. and the mixture was stirred for 30 minutes to obtain solution S5. The reaction rate of the alkenyl group of the compound contained in the obtained solution S5 was calculated as follows: 1 When measured by 1 H-NMR, the reaction rate was 95% or more.
[0134] Next, the solvents (toluene, xylene and 1,4-dioxane) were distilled off under reduced pressure from the solution S5 to obtain a solid content, and then propylene glycol 1-monomethyl ether 2-acetate (hereinafter referred to as "PGMEA") was added to the obtained solid content to obtain a solution SA1 (concentration of the cationic polymerizable compound A1: 70% by mass) containing the cationic polymerizable compound A1. The cationic polymerizable compound A1 was a polymer (weight average molecular weight: 30000) having a plurality of cationic polymerizable groups (specifically, alicyclic epoxy groups) and a plurality of alkali-soluble groups (specifically, X2 groups) in one molecule and having a cyclic polysiloxane structure in the main chain. In addition, the cationic polymerizable compound A1 was soluble in alkali and soluble in organic solvents.
[0135] [Synthesis of cationic polymerizable compound A2] A solution SA2 (concentration of cationic polymerizable compound A2: 70% by mass) containing cationic polymerizable compound A2 was obtained in the same manner as in [Synthesis of cationic polymerizable compound A1], except that 31 g of 1-vinyl-3,4-epoxycyclohexane and 28 g of allyl acrylate were dissolved in 59 g of toluene to obtain solution S4. The cationic polymerizable compound A2 was a polymer (weight average molecular weight: 30,000) having a plurality of cationic polymerizable groups (specifically, alicyclic epoxy groups), a plurality of alkali-soluble groups (specifically, X2 groups), and a plurality of radical polymerizable groups (specifically, acryloyl groups) in one molecule, and having a cyclic polysiloxane structure in the main chain. In addition, the cationic polymerizable compound A2 was soluble in alkali and soluble in organic solvents.
[0136] [Synthesis of cationic polymerizable compound A3] A solution SA3 (concentration of cationic polymerizable compound A3: 70 mass%) containing cationic polymerizable compound A3 was obtained in the same manner as in [Synthesis of cationic polymerizable compound A1], except that 97 μL of a xylene solution of platinum vinylsiloxane complex (Pt-VTSC-3X manufactured by Umicore Precious Metals Japan, a solution containing 3 mass% platinum) was added to a mixture of 40 g of 2,2'-diallyl bisphenol A, 19 g of diallyl monomethyl isocyanurate, and 240 g of 1,4-dioxane to obtain solution S1. The cationic polymerizable compound A3 was a polymer (weight average molecular weight: 30,000) having multiple cationic polymerizable groups (specifically, alicyclic epoxy groups) and multiple alkali-soluble groups (specifically, phenolic hydroxyl groups) in one molecule and having a cyclic polysiloxane structure in the main chain. The cationic polymerizable compound A3 was also alkali-soluble and organic solvent-soluble.
[0137] [Synthesis of alkali-soluble compound A4] SA4 (concentration of alkali-soluble compound A4: 70% by mass) containing alkali-soluble compound A4 was obtained in the same manner as in [Synthesis of cationic polymerizable compound A1], except that S4 was not used. The alkali-soluble compound A4 was a polymer (weight average molecular weight: 30,000) that did not have a cationic polymerizable group in one molecule, had multiple alkali-soluble groups (specifically, X1 group) in one molecule, and had a cyclic polysiloxane structure in the main chain. In addition, the alkali-soluble compound A4 was alkali-soluble and soluble in organic solvents. (To be precise, A4 does not correspond to component (A) because it does not have a cationic polymerizable group.)
[0138] <Preparing other ingredients> In addition to the above solutions SA1 to SA4, the following materials were prepared as materials for the photosensitive compositions. Note that all of the photoradical polymerization initiators described below were compounds that did not generate cations when subjected to heat treatment in the <Formation of Pattern Film> described later. Ditrimethylolpropane tetraacrylate ("AD-TMP" manufactured by Shin-Nakamura Chemical Co., Ltd., a radical polymerizable compound having four acryloyl groups in one molecule, hereinafter referred to as "AD-TMP") Tris-(2-acryloxyethyl)isocyanurate ("A9300" manufactured by Shin-Nakamura Chemical Co., Ltd., a radical polymerizable compound having three acryloyl groups in one molecule, hereinafter referred to as "A9300") 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate (Daicel Corporation's "Celloxide (registered trademark) 2021P", an epoxy monomer having two alicyclic epoxy groups per molecule, hereinafter referred to as "2021P") Benzophenone-based compound as a photoradical polymerization initiator (BASF's "Omnirad (registered trademark) 651", hereinafter referred to as "651") Aromatic sulfonium salt compounds as photocationic polymerization initiators ("CPI-210S" manufactured by San-Apro Co., Ltd., hereinafter referred to as "CPI-210S") 4-Hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl (manufactured by Evonik, hereafter referred to as "H-TEMPO") as a radical scavenger
[0139] <Preparation of Photosensitive Composition> Solution SA1 containing a cationically polymerizable compound A1, solution SA2 containing a cationically polymerizable compound A2, solution SA3 containing a cationically polymerizable compound A3, or solution SA4 containing an alkali-soluble compound A4 were mixed with other materials in the amounts shown in Tables 1 to 2 to obtain photosensitive compositions used in Examples 1 to 4 and Comparative Examples 1 to 3, respectively.
[0140] <Formation of patterned film> [Examples 1 to 4 and Comparative Examples 1 to 3] Each of the photosensitive compositions shown in Tables 1 to 6 was applied onto a glass plate as a glass substrate using a spin coater so that the thickness of the coating film after pre-baking would be 50 μm, and the coating was pre-baked by heating on a hot plate at a temperature of 85° C. for 10 minutes and then at a temperature of 120° C. for 10 minutes to obtain Sample 1.
[0141] Next, a manual exposure machine (Dainippon Kaken "MA-1300", lamp: high-pressure mercury lamp) was used to expose the sample through a photomask with a lattice-shaped line pattern (vertical direction: line / space = 50 μm / 50 μm, horizontal direction: line / space = 100 μm / 100 μm) with an integrated exposure dose of 3000 mJ / cm 2 The coating film of Sample 1 was exposed to light (specifically, soft contact exposure) by irradiating the coating film with light under the above conditions.
[0142] After the exposure, Sample 1 was left for 1 minute in an atmosphere at 25° C., and then immersed in an aqueous TMAH solution (TMAH concentration: 2.38% by mass) as an alkaline developer for 60 seconds. Sample 1 immersed in the alkaline developer was then washed with water for 30 seconds, and the moisture on the surface was removed with compressed air to obtain Sample 2 having a semi-cured patterned film in which the coating film was patterned in a lattice shape.
[0143] <Evaluation> [Reworkability] Sample 2 was brought into contact with an alumina ceramic substrate via a pattern film, and a 2 kg weight was placed on a hot plate at 80°C for 30 seconds to bond the substrate. The laminate was then placed on a hot plate at 100°C for 30 seconds, and the glass substrate was picked up with tweezers to evaluate the reworkability. The reworkability was evaluated according to the following criteria based on the state after the rework test. If the evaluation was A or B, the substrate was evaluated as having "excellent reworkability." On the other hand, if the evaluation was C, the substrate was evaluated as having "poor reworkability."
[0144] (Criteria for determining reworkability) A: It is peelable and the pattern film does not remain on the alumina ceramic substrate. B: Peelable, but part of the pattern film remains on the alumina ceramic substrate C: Cannot be peeled off, or peelable but most of the pattern film remains on the alumina ceramic substrate
[0145] [Adhesion after full curing] Sample 2 was brought into contact with an alumina ceramic substrate via a patterned film, and a 2 kg weight was placed on a hot plate at 80°C for 30 seconds to allow adhesion. It was then heated in an oven at 200°C for 2 hours to allow for full curing. The resulting laminate was used to bounce a glass substrate with a die shear tester, and the die shear strength was measured to evaluate adhesion. The detailed measurement conditions are as follows: Measurement equipment: Bond tester (DAGE "4000Plus") Measurement temperature: 23℃ Shear speed: 0.1μm / sec
[0146] (Criteria for determining adhesiveness after full curing) The adhesiveness after full curing was judged according to the following criteria based on the measured die shear strength. If the rating was A or B, it was evaluated as "excellent adhesiveness after full curing." On the other hand, if the rating was C, it was evaluated as "not excellent adhesiveness after full curing." A: Die shear strength is 10kgf or more B: Die shear strength is 5kgf or more and less than 10kgf C: Die shear strength is less than 5kgf
[0147] <Result> Tables 1 and 2 show the composition of the photosensitive composition used, the surface elastic modulus, Tg, reaction initiation temperature, reworkability, and the evaluation results of adhesion after main curing for Examples 1 to 4 and Comparative Examples 1 to 3, respectively. In Tables 1 and 2, the blending amount is the blending amount (unit: parts by mass) relative to 100 parts by mass of the cationic polymerizable compound. In Tables 1 and 2, the blending amount of PGMEA includes the amount of PGMEA in Solution SA1, Solution SA2, Solution SA3, or Solution SA4. In Tables 1 and 2, "-" in the column "Composition of photosensitive composition" means that the component in question was not blended.
[0148] [Table 1]
[0149] [Table 2]
[0150] The photosensitive compositions used in Examples 1 to 4 contained a cationic polymerizable compound, a radical polymerizable compound having a (meth)acryloyl group, and a photopolymerization initiator. In the photosensitive compositions used in Examples 1 to 4, the photopolymerization initiator was a photoradical polymerization initiator. In the photosensitive compositions used in Examples 1 to 4, the cationic polymerizable compound had a cationic polymerizable group and an alkali-soluble group in one molecule. In the photosensitive compositions used in Examples 1 to 4, the amount of the radical polymerizable compound was 5 parts by mass or more relative to 100 parts by mass of the cationic polymerizable compound.
[0151] In Examples 1 to 4, the reworkability was evaluated as A or B. Thus, rework was possible in Examples 1 to 4. In Examples 1 to 4, the adhesiveness after main curing was evaluated as A or B. Thus, Examples 1 to 4 had high adhesiveness after main curing.
[0152] The photosensitive composition used in Comparative Example 1 did not contain a radical polymerizable compound having a (meth)acryloyl group and a photoradical polymerization initiator. The photosensitive compositions used in Comparative Examples 2 and 3 contained a photoradical polymerization initiator as a photopolymerization initiator. The photosensitive compositions used in Comparative Examples 2 and 3 did not contain a cationic curable compound.
[0153] In Comparative Example 1, the reworkability was evaluated as C. Thus, Comparative Example 1 was not reworkable. In Comparative Examples 2 and 3, the adhesiveness after main curing was evaluated as C. Thus, Comparative Examples 2 and 3 had insufficient adhesiveness after main curing.
[0154] The above results demonstrate that the use of the photosensitive composition according to the present invention makes it possible to provide a lamination process for a reworkable substrate laminate. [Explanation of symbols]
[0155] 10 Substrate laminate 11 First board 12 Second board 13 Cured material layer 14 Coating 14a Exposure section 14b Non-exposed area 15 Patterned film (patterned coating film) 16 Laminate
Claims
1. A patterned film-bearing substrate having a patterned coating film on a first substrate, The patterned film-formed substrate is intended to be laminated with a second substrate via a patterned coating film to obtain a substrate laminate for a solid-state imaging device; the patterned film-bearing substrate is laminated with a second substrate via the patterned coating film, and then the patterned coating film and the second substrate are heated to a temperature of 50° C. or more and less than 150° C., whereby the patterned coating film and the second substrate can be peeled off from each other; A substrate with a patterned film for a solid-state imaging device, in which a laminate of a substrate with a patterned film and a second substrate is heated to 150° C. or higher to fully cure the patterned coating film and improve adhesion.
2. the patterned coating film is made of a photosensitive composition, the photosensitive composition contains a cationic polymerizable compound, a radical polymerizable compound, and a photopolymerization initiator, and the photopolymerization initiator is a photoradical initiator; The radical polymerizable compound has a (meth)acryloyl group, 2 . The substrate with a patterned film for a solid-state imaging device according to claim 1 , wherein an amount of the radically polymerizable compound is 5 parts by mass or more with respect to 100 parts by mass of the cationically polymerizable compound.
3. The method for producing a substrate laminate for a solid-state imaging device according to claim 2 , wherein an amount of the radical polymerizable compound is 200 parts by mass or less with respect to 100 parts by mass of the cationically polymerizable compound.
4. The substrate with a patterned film for a solid-state imaging device according to claim 2 , wherein the cationic polymerizable compound has a polysiloxane structure.
5. 3. The substrate with a patterned film for a solid-state imaging device according to claim 2, wherein the cationically polymerizable compound contains, as a cationically polymerizable group, at least one of an alicyclic epoxy group, a glycidyl group, and an oxetanyl group.
6. 3. The substrate with a patterned film for a solid-state imaging device according to claim 2, wherein the radical polymerizable compound has an isocyanuric ring and the (meth)acryloyl group in one molecule.
7. 3. The substrate with a patterned film for a solid-state imaging device according to claim 2, wherein the alkali-soluble group in the cationically polymerizable compound is at least one selected from the group consisting of a monovalent organic group represented by the following chemical formula (X1), a divalent organic group represented by the following chemical formula (X2), and a phenolic hydroxyl group: 【Chemistry 1】
8. 2. The substrate with a patterned film for a solid-state imaging device according to claim 1, wherein the first substrate is a glass substrate, and the second substrate is a semiconductor device substrate.
Citation Information
Patent Citations
Substrate laminate and image sensor using the same
JP2019062048A
